Process improvement analysis in toll corridor development with lean six sigma approach: case in PT Jasamarga Related Business - Batubara, David Perkasa; Rouli, Juliana (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
Toll Corridor Development (TCD) is one of the businesses conducted by PT Jasamarga Related Business as a follow-up to the issuance of Peraturan Menteri Pekerjaan Umum dan Perumahan Rakyat (PUPR) No. 28 of 2021. In the development of its first TCD project, Jasamarga Related Business (JMRB) encountered issues that resulted in the delay of the project's completion. The purpose of this research is to analyze and make improvements to the causes of delays in the Taman Mini TCD project. In this research, the lean six sigma approach is used to analyze process improvements that can be carried out so that these problems can be minimized in the further development of TCD. To identify activities that cause delays in the implementation of this project, the critical path method (CPM) was used based on the results of interviews with those directly involved in the development of TCD project. From the activities that cause the delay, a causal analysis is carried out using a fishbone diagram, and then an analysis of possible improvements is carried out using a lean concept approach. Based on the analysis results, three main issues are identified, namely inadequate planning process, ineffective partner or consultant selection process and delays in construction completion. From the cause-and-effect analysis, it can be concluded that potential improvements can be made by implementing the concept of pull planning, improving the business process by reducing waste and enhancing value-added activities, establishing effective stakeholder management, and maximizing the use of technology-based applications to aid project control.